Prehistoric Argyll - Report on the Exploration of a Burial Cairn at Balnabraid, Kintyre - Lindsay Galloway, Mrs T; Bryce, Thomas (Proceedings of the Society of Antiquaries of Scotland, 1920)
The cairn appears to be oval although almost half has been washed away by an adjacent burn. The whole of the surviving cairn was investigated. The burials lie at somewhat different levels, and were both cisted and uncisted; and a much disturbed passage chamber and a portion of a marginal setting of stones were revealed. The cists numbered twelve and are described in detail. In the main they contained cremated human bone although skeletons were present in a few. One cist contained both burnt and unburnt bone. Artefacts included food vessels, jet beads, bronze sheeting, beakers and a flint knife. The interior of the cairn was almost entirely composed of loose stones, amongst which at various places were noticed small collections of human osseous remains. In most cases these were inhumed and not associated with any special arrangement of the stones. There were also a few isolated fragments of bones, mostly unburnt, and a few cremated. The article includes a report on the human bone.